2012
DOI: 10.1148/radiol.12120422
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Aneurysms: Midterm Outcome of Pipeline Embolization Device—A Prospective Study in 143 Patients with 178 Aneurysms

Abstract: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.12120422/-/DC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
134
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(150 citation statements)
references
References 18 publications
10
134
1
5
Order By: Relevance
“…In most series, remarkably high rates of aneurysm occlusion were achieved at follow-up with an acceptable risk for major complications. [1][2][3][4][5] Some authors, based on favorable results from noncontrolled series, have even recommended the PED as a first-line option for unruptured aneurysms. 3 Long-term safety results, however, are lacking and new complications have been emerging as neurointerventionalists accumulate experience with the device.…”
Section: Discussionmentioning
confidence: 99%
“…In most series, remarkably high rates of aneurysm occlusion were achieved at follow-up with an acceptable risk for major complications. [1][2][3][4][5] Some authors, based on favorable results from noncontrolled series, have even recommended the PED as a first-line option for unruptured aneurysms. 3 Long-term safety results, however, are lacking and new complications have been emerging as neurointerventionalists accumulate experience with the device.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many studies have reported higher occlusion rates among CCA subgroups. 6,27 This extra success afforded to the cavernous segment is likely multifold. Even though this carotid segment is usually tortuous, there were no major bifurcations occurring on it, which resulted in lower wall sheer stress on the vessel wall and less blood flow through the stent.…”
Section: Flow Diversion For Ccasmentioning
confidence: 99%
“…A study on 251 aneurysms treated with PED demonstrated permanent morbidity and mortality of only 1% and 0.5%, respectively (15). Yu et al reported a complete aneurysm occlusion rate of 84% in a multicenter study with peri-procedural death or stroke seen in 3.5% (16). They suggested PED to be the first line choice for treating un-ruptured intracranial aneurysms.…”
Section: Discussionmentioning
confidence: 99%